SAGA1 and SAGA2 localize the starch sheath to the pyrenoid in Chlamydomonas reinhardtii - Victoria L. Crans; Micah I. Burton; Aastha Garde; Lianyong Wang; Martin C. Jonikas (Proceedings of the National Academy of Sciences, 2026)
Most algae enhance their CO 2 assimilation by concentrating CO 2 within the pyrenoid, a biomolecular condensate of the CO 2 -fixing enzyme Rubisco. Many pyrenoids are surrounded by a starch sheath thought to slow the escape of CO 2 from the pyrenoid, but how the starch sheath is localized to the pyrenoid remains poorly understood. Here, in the model alga Chlamydomonas reinhardtii , we find that the protein SAGA2 is necessary for early pyrenoid starch sheath biogenesis and works redundantly with its homolog, SAGA1, to localize the starch sheath to the pyrenoid. SAGA2 and SAGA1 were enriched in different regions of the pyrenoid–starch sheath interface: SAGA1 at pyrenoid tubule-associated puncta and SAGA2 along the rest of the interface, suggesting that SAGA2 and SAGA1 play complementary roles. Both saga2 and saga1 mutants showed decreased starch sheath coverage early during pyrenoid formation that was remedied at a later timepoint. Strikingly, a saga1;saga2 double mutant did not have a starch sheath around the pyrenoid at any timepoint. SAGA1 and SAGA2 starch-binding domains bound to starch, the starch mimic β-cyclodextrin, and the starch precursor maltoheptaose, suggesting a role for SAGA1 and SAGA2 in starch granule initiation. We propose a model where SAGA1 and SAGA2 each locally prime starch sheath initiation in a distinct region of the pyrenoid surface by enriching starch precursor molecules around the pyrenoid. These findings advance the understanding of algal starch sheath biogenesis and provide insights into the associations between biomolecular condensates and other cellular structures.